Оценка механизмов упрочнения, формирующих предел текучести в заэвтектоидной стали - Попова, Наталья Анатольевна канд. техн. наук; Громов, Виктор Евгеньевич 1947-; Никоненко, Елена Леонидовна; Иванов, Юрий Федорович 1955-; Порфирьев, Михаил Анатольевич; Шляров, Виталий Владиславович; Крюков, Роман Евгеньевич (Известия высших учебных заведений. Физика)
Transmission electron microscopy was used to study the structural-phase states in the head of the differentially hardened 100-meter rails made of hypereutectoid steel along the central axis at a depth of up to 10 mm after operation on the experimental ring of Russian Railways (the missed tonnage of 187 million gross tons). It is shown that the strength of steel is determined by the combined action of a number of physical mechanisms. A quantitative assessment of the contributions to the hardening from the friction of the crystal lattice, solid solution hardening, hardening of the pearlite component by cementite particles, grain boundaries and subboundaries, scalar and excess dislocation density is carried out and their hierarchy is established. The dependence of the additive yield strength on the distance to the tread surface of the rail head is established.